High-temperature lithium ion electrolyte and preparation method thereof

By using a specific composition of high-temperature lithium-ion electrolyte in lithium-ion batteries, the problem of long-cycle performance decay in high-temperature environments is solved, and efficient circulation performance and thermal expansion resistance are achieved at high temperatures.

CN119297403APending Publication Date: 2025-01-10SICHUAN DINGRUI NEW MATERIAL TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411385137.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The long-cycle performance of existing lithium-ion batteries rapidly decays in high-temperature environments, making it difficult to meet the working needs in high-temperature environments.

Method used

A high-temperature lithium-ion electrolyte is adopted, including non-aqueous organic solvents, lithium salts and additives. The specific composition includes vinyl carbonate, chlorinated vinyl carbonate, trifluoropropylene carbonate, lithium hexafluorophosphate, lithium dioxalate borate, and difluoro Lithium sulfonimide, Si(OCH2CF3)4, 1-[2-(trisilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 2,3-pyridine dicarboxylic anhydride, through these The synergistic effect of components improves the circulation performance and thermal expansion resistance of lithium-ion batteries at high temperatures.

Benefits of technology

The battery capacity retention rate of the electrolyte for 600 weeks is not less than 93.7%, and the battery capacity retention rate for 100 weeks is not less than 97.8%, and it can effectively suppress the battery expansion rate at high temperature and improve the battery's Cycle stability and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-temperature lithium ion electrolyte and a preparation method thereof, and belongs to the technical field of electrolyte preparation. Comprising a non-aqueous organic solvent, a lithium salt and an additive, the non-aqueous organic solvent comprises vinylene carbonate, chloroethylene carbonate and trifluoropropene carbonate; the lithium salt comprises lithium hexafluorophosphate, lithium bis (oxalato) borate and lithium bis (fluorosulfonyl) imide; the additive is prepared from Si (OCH2CF3) 4, 1-[2-(trimethylsilyl) ethyoxyl carbonyloxy] pyrrolidine-2, 5-diketone and 2, 3-dipicolinic acid anhydride; the preparation method comprises the following steps: uniformly mixing vinylene carbonate, chloroethylene carbonate and trifluoropropene carbonate to obtain a non-aqueous organic solvent; the preparation method comprises the following steps: firstly, adding lithium hexafluorophosphate, lithium bis (oxalato) borate and lithium bis (fluorosulfonyl) imide, fully stirring, then adding Si (OCH2CF3) 4, 1-[2-(trimethylsilyl) ethoxycarbonyloxy] pyrrolidine-2, 5-diketone and 2, 3-dipicolinic acid anhydride, and fully stirring to obtain an electrolyte; the electrolyte can improve the high-temperature long cycle performance and thermal expansion performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolyte preparation, and specifically relates to a high-temperature lithium ion electrolyte and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life and good environmental protection, and are considered to be the first choice for green and environmentally friendly batteries.

[0003] However, most lithium-ion batteries (with lithium hexafluorophosphate as electrolyte) on the market will experience rapid attenuation of long-term cycling performance under high temperature and high pressure for long-term charging and discharging, and the capacity will be greatly reduced during long cycles. For example, Strehle et al. (STREHLE B, FRIEDRICH F, GASTEIGER HA. A comparative study of structural changes during long~term cycling of NCM~811 at ambient and elevated temperatures[J]. Journalof the Electrochemical Society, 2021, 168(5): 050512) systematically compared the long-term cycling performance of Li(Ni0.8Co0.1Mn0.1)O2 / graphite at room temperature and elevated temperature (22 ℃ and 45 ℃). The capacity of the battery after 700 cycles at high temperature of 45 ℃ (139 mAh / g) is much lower than the capacity after 1000 cycles at room temperature of 22 ℃ (145 mAh / g).

[0004] Based on this, most lithium-ion batteries in the prior art are difficult to meet the working requirements in high temperature environments.

[0005] As an important component of the battery, lithium-ion electrolyte plays the role of transporting lithium ions between the positive and negative electrodes of the lithium-ion battery, and is known as the "blood" of the lithium-ion battery. Lithium-ion electrolyte plays a vital role in the battery's specific capacity, operating temperature range, cycle efficiency and safety performance.

[0006] Therefore, it is extremely important to provide a lithium ion electrolyte that can effectively improve the long cycle performance requirements of lithium ion batteries at high temperatures. Summary of the invention

[0007] The purpose of the present invention is to provide a high-temperature lithium-ion electrolyte and a preparation method thereof for the first time; the lithium-ion electrolyte can effectively improve the high-temperature and long-cycle performance of lithium-ion batteries.

[0008] The purpose of the present invention is achieved through the following technical solutions: A high temperature lithium ion electrolyte comprising the following components: including non-aqueous organic solvents, lithium salts and additives; The non-aqueous organic solvent includes vinylene carbonate, chloroethylene carbonate and trifluoropropylene carbonate; The lithium salt includes lithium hexafluorophosphate, lithium bis(oxalatoborate), and lithium bis(fluorosulfonyl)imide; The additives include Si(OCH2CF3)4, 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 2,3-pyridinedicarboxylic anhydride.

[0009] As one of the embodiments of the present application, the high temperature lithium ion electrolyte includes the following components in parts by weight: 20-35 parts of vinylene carbonate, 15-25 parts of chloroethylene carbonate, 15-25 parts of trifluoropropylene carbonate, 10-20 parts of lithium hexafluorophosphate, 1-5 parts of lithium bis(oxalatoborate), 1-5 parts of lithium bis(fluorosulfonyl)imide, 0.1-5 parts of Si(OCH2CF3)4, 0.1-5 parts of 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 0.1-5 parts of 2,3-pyridinedicarboxylic anhydride.

[0010] As one of the embodiments of the present application, the high temperature lithium ion electrolyte includes the following components in parts by weight: 22-33 parts of vinylene carbonate, 16-24 parts of chloroethylene carbonate, 16-23 parts of trifluoropropylene carbonate, 13-20 parts of lithium hexafluorophosphate, 1.5-3.5 parts of lithium bis(oxalatoborate), 1.5-3.5 parts of lithium bis(fluorosulfonyl)imide, 0.5-3 parts of Si(OCH2CF3)4, 0.5-3 parts of 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 0.5-3 parts of 2,3-pyridinedicarboxylic anhydride.

[0011] As one of the embodiments of the present application, the high temperature lithium ion electrolyte includes the following components in parts by weight: 25-32 parts of vinylene carbonate, 18-20 parts of chloroethylene carbonate, 18-20 parts of trifluoropropylene carbonate, 15-18 parts of lithium hexafluorophosphate, 2-3 parts of lithium bis(oxalatoborate), 1.8-3 parts of lithium bis(fluorosulfonyl)imide, 1-2 parts of Si(OCH2CF3)4, 1-2 parts of 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 1-2 parts of 2,3-pyridinedicarboxylic anhydride.

[0012] As one possible embodiment of the present application, the high temperature lithium ion electrolyte further includes 0.2 to 5 parts of a fluorinated ether compound.

[0013] As one possible embodiment of the present application, the fluorinated ether compound is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0014] As one possible embodiment of the present application, the fluorinated ether compound is replaced by a modified fluorinated ether compound, wherein the modified fluorinated ether compound is a fluorinated ether compound modified by acrylonitrile or vinyl carbonate.

[0015] As one of the embodiments of the present application, the preparation method of the modified fluorinated ether compound is as follows: First, add the fluorinated ether compound and azobisisobutyronitrile to an organic solvent, stir thoroughly, then add acrylonitrile or ethylene carbonate, and react thoroughly at 30-40°C for 3-5 hours. After removing the solvent, a modified fluorinated ether compound is obtained.

[0016] In addition, to achieve the above-mentioned purpose, the present application also provides a method for preparing a high-temperature lithium-ion electrolyte, comprising the following steps: S1. vinylene carbonate, chloroethylene carbonate, trifluoropropylene carbonate and a fluorinated ether compound are uniformly mixed to obtain a non-aqueous organic solvent; S2 In an inert gas environment at room temperature, lithium hexafluorophosphate, lithium dioxalatoborate and lithium bis(fluorosulfonyl)imide are added to a non-aqueous organic solvent and stirred until the composite lithium salt is completely dissolved; then Si(OCH2CF3)4, 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 2,3-pyridinedicarboxylic acid anhydride are added, stirred thoroughly and allowed to stand to obtain a lithium ion electrolyte.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The electrolyte provided in the present application can improve the high temperature and long cycle performance of the battery. The battery capacity retention rate after 600 cycles at 45°C is not less than 93.7%; the battery capacity retention rate after 100 cycles at 60°C is not less than 97.8%; the battery capacity retention rate after 200 cycles at 60°C is not less than 92.3%; and the battery capacity retention rate after 300 cycles at 60°C is not less than 82.2%.

[0018] The electrolyte provided in the present application can improve the thermal expansion resistance of the battery. In a continuous high-temperature charging test experiment at 60°C, the battery cell expansion rate on the 6th day is no more than 4.7%, the battery cell expansion rate on the 12th day is no more than 7.5%, and the battery cell expansion rate on the 18th day is no more than 13.3%. DETAILED DESCRIPTION

[0019] In the prior art, most lithium-ion batteries on the market use LiPF6 electrolyte systems, which have the advantages of good solubility, high ion conductivity, high ion dissociation, and the ability to form a relatively stable SEI film. However, this electrolyte is too sensitive to moisture and has poor thermal stability, resulting in an unstable passivation film formed at high temperatures. Under high temperature and high pressure and long-term charging and discharging, its long-cycle performance will decay rapidly, and the capacity will be greatly reduced during the long cycle, making it difficult to meet the working requirements in high temperature environments.

[0020] Based on this, the present application provides a high-temperature lithium-ion electrolyte, comprising the following components: including non-aqueous organic solvents, lithium salts and additives; The non-aqueous organic solvent includes vinylene carbonate, chloroethylene carbonate and trifluoropropylene carbonate; The lithium salt includes lithium hexafluorophosphate, lithium bis(oxalatoborate), and lithium bis(fluorosulfonyl)imide; The additives include Si(OCH2CF3)4, 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 2,3-pyridinedicarboxylic anhydride.

[0021] In the above scheme, LiPF6 is used as the main lithium salt in the lithium salt system, and LiBOB is added on this basis. It has good thermal stability and electrochemical stability, and can effectively improve the thermal stability of the lithium salt system. In addition, O in the oxalate group can disperse all the electrons of B, thereby reducing the interaction between lithium ions and BOB~ and improving the degree of dissociation in the solvent; further, BOB- can further form a SEI film on the basis of LiPF6, improving the safety and stability of the SEI film. However, the ionic conductivity of LiBOB is not high, and the resulting SEI film has a large impedance problem.

[0022] Based on this, the present application adds lithium bis(fluorosulfonyl)imide, which has the characteristics of high thermal stability, ion conductivity and higher lithium ion migration number, and can effectively improve the technical problem of low conductivity of LiBOB. At the same time, the addition of LiFSI can increase the lithium ion migration number of the electrolyte and reduce the concentration polarization of the battery, thereby improving the reversibility of the electrode reaction; in addition, the addition of LiFSI can reduce the impedance of the electrolyte / electrode interface, thereby improving the technical problem of high impedance of the SEI film generated by LiBOB; in addition, LiFSI can not only form a stable SEI film on the surface of the negative electrode, but also help to form a stable CEI film on the surface of LiFePO4; further, LiBOB can effectively improve the corrosion of LiFSI on the aluminum foil current collector.

[0023] This application adds LiBOB and LiFSI9 (both are expensive, and adding too much can easily lead to increased viscosity and increased impedance) to lithium hexafluorophosphate, which can effectively improve the safety and stability of the SEI film and CEI film of the LiPF6 electrolyte system, and improve its high-temperature long-cycle performance compared to the LiPF6 electrolyte system. For example, under the test conditions of 3.0-4.45V and 50°C, the discharge capacity retention rate after 300 cycles can reach 99.42%; however, when the temperature rises, such as the temperature rises to 65°C, the high temperature environment will cause the SEI film and CEI film and the positive and negative electrode structures to be severely damaged, resulting in the loss of positive and negative electrode active materials, as well as the loss of electrolyte, which in turn causes the battery capacity to decay sharply, and the discharge capacity retention rate drops to below 70% after 150 cycles. One of the important reasons for the degradation of the above-mentioned battery performance is the hydrogen fluoride produced by the decomposition of lithium salts, which will cause changes in the metal ion solution in the positive electrode material of the lithium-ion battery, affecting the surface structure of the positive electrode material of the lithium-ion battery, and thus affecting the cycle performance. In addition, other production will occur in a high temperature environment, which will further aggravate the expansion of the battery and affect the electrical performance.

[0024] Based on this, the present invention adds 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and Si(OCH2CF3)4 to the above system.

[0025] 1-[2-(Trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione can eliminate HF and other gases produced by the hydrolysis of lithium salts, effectively reduce the degree of damage caused by the gas to the positive electrode structure and the enrichment at the negative electrode, thereby effectively reducing the expansion of the battery caused by gas production in a high temperature environment; although 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione can eliminate HF, the CEI film will still cause a certain degree of damage, and the protection strength of the positive electrode structure will be reduced. Based on this, the added Si(OCH2CF3)4 can continuously form a dense, stable, low-impedance CEI film on the surface of the positive electrode, thereby improving the protection of the positive electrode, and thereby improving the cycle stability of the battery under high temperature and high pressure.

[0026] After adding the above substances, the high-temperature and long-cycle performance of the battery can be effectively improved. However, during the high-temperature cycle of the battery, the internal degradation of the battery causes capacity decay and impedance increase, causing the electrolyte to undergo redox reactions and produce gas. The consumption of the electrolyte causes the electrode to dry up locally, and the gas changes the distance between the electrodes, causing uneven current during the recharging process of the battery, resulting in lithium precipitation. The electrolyte will show obvious degassing. At the same time, it will cause lithium pitting on the battery cell and increase the thickness expansion rate of the battery, seriously affecting the battery performance.

[0027] Based on this, the present invention further adds 2,3-pyridinedicarboxylic anhydride to the above components, which can broaden the redox window of the electrolyte and form a passivation film on the surface of the positive and negative electrodes before the solvent, effectively improving the high-temperature stability of the SEI film and the CEI film, effectively inhibiting the decomposition of the electrode liquid and the interfacial side reactions, etc., thereby improving the cycle performance of the battery under high temperature and high pressure, etc., and effectively inhibiting the high-temperature thickness expansion rate.

[0028] In addition, on the basis of the above components, the present application adds chloroethylene carbonate and trifluoropropylene carbonate to the non-aqueous organic solvent, which not only participate in the formation of the positive and negative electrode passivation films, but also can effectively improve the cycle performance of the battery.

[0029] Through the synergistic effect of the above components, the cycle performance of the battery can be effectively improved, and the high temperature thickness expansion rate of the battery can be reduced. Specifically, In order to effectively improve the cycle performance of the battery at high temperature, as one of the embodiments of the present application, the weight percentage of each component in the high temperature lithium ion electrolyte is further limited, that is, the high temperature lithium ion electrolyte includes the following components by weight: 20-35 parts of vinylene carbonate, 15-25 parts of chloroethylene carbonate, 15-25 parts of trifluoropropylene carbonate, 10-20 parts of lithium hexafluorophosphate, 1-5 parts of lithium bis(oxalatoborate), 1-5 parts of lithium bis(fluorosulfonyl)imide, 0.1-5 parts of Si(OCH2CF3)4, 0.1-5 parts of 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 0.1-5 parts of 2,3-pyridinedicarboxylic anhydride.

[0030] In this solution, by limiting the weight fraction of each component in the electrolyte, it is possible to ensure that the viscosity, ion mobility, conductivity, etc. of the electrolyte are at the optimum level, effectively avoiding the increase in impedance or viscosity due to excessive addition of some components, which affects the decrease in conductivity (such as excessive addition of lithium bis(fluorosulfonyl)imide), decrease in ion mobility, or lithium precipitation (such as excessive addition of 2,3-pyridinedicarboxylic anhydride), etc. In order to effectively improve the cycle performance of the battery at high temperature, as one of the embodiments of the present application, the weight percentage of each component in the high temperature lithium ion electrolyte is further limited, that is, the high temperature lithium ion electrolyte includes the following components by weight: 22-33 parts of vinylene carbonate, 16-24 parts of chloroethylene carbonate, 16-23 parts of trifluoropropylene carbonate, 13-20 parts of lithium hexafluorophosphate, 1.5-3.5 parts of lithium bis(oxalatoborate), 1.5-3.5 parts of lithium bis(fluorosulfonyl)imide, 0.5-3 parts of Si(OCH2CF3)4, 0.5-3 parts of 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 0.5-3 parts of 2,3-pyridinedicarboxylic anhydride.

[0031] In order to effectively improve the cycle performance of the battery at high temperature, as one of the embodiments of the present application, the weight percentage of each component in the high temperature lithium ion electrolyte is further limited, that is, the high temperature lithium ion electrolyte includes the following components by weight: 25-32 parts of vinylene carbonate, 18-20 parts of chloroethylene carbonate, 18-20 parts of trifluoropropylene carbonate, 15-18 parts of lithium hexafluorophosphate, 2-3 parts of lithium bis(oxalatoborate), 1.8-3 parts of lithium bis(fluorosulfonyl)imide, 1-2 parts of Si(OCH2CF3)4, 1-2 parts of 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 1-2 parts of 2,3-pyridinedicarboxylic anhydride.

[0032] In order to effectively improve the cycle performance of the battery at high temperature, as one of the embodiments of the present application, the composition of the high-temperature lithium-ion electrolyte is further limited, that is, the high-temperature lithium-ion electrolyte also includes 0.2 to 5 parts of fluorinated ether compounds.

[0033] After adding fluorinated ether compounds, the flame retardancy and high-temperature stability of the electrolyte can be effectively improved; in addition, the fluorinated ether compounds can improve the composition and morphology of the SEI film, improve the structural stability of the SEI film, and can also improve the technical problem of capacity attenuation caused by the increased impedance of the electrolyte additives after multiple cycles of discharge of the battery.

[0034] In order to effectively improve the cycle performance of the battery at high temperature, as one of the possible embodiments of the present application, the fluorinated ether compound is further limited, that is, the fluorinated ether compound is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0035] In order to effectively improve the compatibility of the components in the electrolyte and improve the cycle performance of the battery, as one of the embodiments of the present application, the fluorinated ether compound is further limited, that is, the modified fluorinated ether compound is a fluorinated ether compound modified by acrylonitrile or ethylene carbonate. Specifically, the preparation method of the modified fluorinated ether compound is as follows: First, add the fluorinated ether compound and azobisisobutyronitrile to an organic solvent, stir thoroughly, then add acrylonitrile or ethylene carbonate, and react thoroughly at 30-40°C for 3-5 hours. After removing the solvent, a modified fluorinated ether compound is obtained.

[0036] Due to the poor compatibility of fluorinated ether compounds with LiPF6, the impedance between the two interfaces is large, which in turn affects the uniform stability of the entire electrolyte, and has an adverse effect on the stable migration of ions and conductivity. Based on this, the present application modifies fluorinated ether compounds, which can effectively improve their compatibility with LiPF6, thereby improving the compatibility and uniformity of the components in the electrolyte, and effectively solving the technical problems of difficult stable migration of ions and low conductivity due to the interface impedance between the two.

[0037] In order to effectively improve the cycle performance of the battery at high temperature, as one of the embodiments of the present application, the preparation method of the modified fluorinated ether compound is further limited, that is, the preparation method of the modified fluorinated ether compound is as follows: First, add the fluorinated ether compound and azobisisobutyronitrile into an organic solvent, stir thoroughly and then add the polymer monomer, then fully react at 30-40°C for 3-5h, remove the solvent and obtain the modified fluorinated ether compound.

[0038] In addition, to achieve the above-mentioned purpose, the present application also provides a method for preparing a high-temperature lithium-ion electrolyte, comprising the following steps: S1. vinylene carbonate, chloroethylene carbonate, trifluoropropylene carbonate and a fluorinated ether compound are uniformly mixed to obtain a non-aqueous organic solvent; S2 In an inert gas environment at room temperature, lithium hexafluorophosphate, lithium dioxalatoborate and lithium bis(fluorosulfonyl)imide are added to a non-aqueous organic solvent and stirred until the composite lithium salt is completely dissolved; then Si(OCH2CF3)4, 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 2,3-pyridinedicarboxylic acid anhydride are added, stirred thoroughly and allowed to stand to obtain a lithium ion electrolyte.

[0039] It is worth noting that in the above preparation method, the fluorinated ether compound can be replaced by a modified fluorinated ether compound to obtain a more uniform and stable electrolyte.

[0040] Next, the preparation method of the high-temperature lithium-ion electrolyte in the present application is described in detail through examples.

[0041] Example 1 S1. 30 parts of vinylene carbonate, 23 parts of chloroethylene carbonate, 18 parts of trifluoropropylene carbonate and 1 part of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether are mixed uniformly to obtain a non-aqueous organic solvent; S2: Under an inert gas environment at room temperature, 18 parts of lithium hexafluorophosphate, 2 parts of lithium dioxalate borate, and 1 part of lithium bis(fluorosulfonyl)imide are added to a non-aqueous organic solvent and stirred until the composite lithium salt is completely dissolved; then 2 parts of Si(OCH2CF3)4, 1.5 parts of 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 1 part of 2,3-pyridinedicarboxylic anhydride are added, stirred sufficiently, and allowed to stand to obtain a lithium ion electrolyte. The water content and acidity of the electrolyte meet the GB / T 19282-2014 standard.

[0042] Example 2 S1 33 parts of vinylene carbonate, 18 parts of chloroethylene carbonate, 20 parts of trifluoropropylene carbonate and 1.1 parts of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether are mixed uniformly to obtain a non-aqueous organic solvent; S2: Under an inert gas environment at room temperature, 20 parts of lithium hexafluorophosphate, 1.5 parts of lithium dioxalate borate, and 1.5 parts of lithium bis(fluorosulfonyl)imide are added to a non-aqueous organic solvent and stirred until the composite lithium salt is completely dissolved; then 2 parts of Si(OCH2CF3)4, 2 parts of 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 1 part of 2,3-pyridinedicarboxylic anhydride are added, stirred sufficiently, and allowed to stand to obtain a lithium ion electrolyte. The water content and acidity of the electrolyte meet the GB / T 19282-2014 standard.

[0043] Example 3 S1. 32 parts of vinylene carbonate, 18 parts of chloroethylene carbonate, 20 parts of trifluoropropylene carbonate and 1.5 parts of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether are mixed uniformly to obtain a non-aqueous organic solvent; S2: Under an inert gas environment at room temperature, 18 parts of lithium hexafluorophosphate, 2 parts of lithium dioxalate borate, and 1.8 parts of lithium bis(fluorosulfonyl)imide are added to a non-aqueous organic solvent and stirred until the composite lithium salt is completely dissolved; then 2 parts of Si(OCH2CF3)4, 1.8 parts of 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 1.2 parts of 2,3-pyridinedicarboxylic anhydride are added, stirred sufficiently, and allowed to stand to obtain a lithium ion electrolyte. The water content and acidity of the electrolyte meet the GB / T 19282-2014 standard.

[0044] Example 4 S1. 32 parts of vinylene carbonate, 18 parts of chloroethylene carbonate, 20 parts of trifluoropropylene carbonate and 2 parts of modified fluorinated ether compound are mixed uniformly to obtain a non-aqueous organic solvent; S2: Under an inert gas environment at room temperature, 18 parts of lithium hexafluorophosphate, 2 parts of lithium dioxalate borate, and 1.8 parts of lithium bis(fluorosulfonyl)imide are added to a non-aqueous organic solvent and stirred until the composite lithium salt is completely dissolved; then 2 parts of Si(OCH2CF3)4, 1.8 parts of 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 1.2 parts of 2,3-pyridinedicarboxylic anhydride are added, stirred sufficiently, and allowed to stand to obtain a lithium ion electrolyte. The water content and acidity of the electrolyte meet the GB / T 19282-2014 standard.

[0045] Wherein, the preparation method of the modified fluorinated ether compound is as follows: First, add 1g 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 0.02g azobisisobutyronitrile to 250-300mL n-hexane, stir thoroughly and then add 0.5g ethylene carbonate monomer, then react at 30-40°C for 3-5h, and remove the solvent to obtain the modified fluorinated ether compound.

[0046] Comparative Example 1 S1. 32 parts of vinylene carbonate, 18 parts of chloroethylene carbonate, 20 parts of trifluoropropylene carbonate and 1.5 parts of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether are mixed uniformly to obtain a non-aqueous organic solvent; S2 Under an inert gas environment at room temperature, add 20 parts of lithium hexafluorophosphate to a non-aqueous organic solvent and stir until the complex lithium salt is completely dissolved; then add 2 parts of Si(OCH2CF3)4, 1.8 parts of 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 1.2 parts of 2,3-pyridinedicarboxylic acid anhydride, stir thoroughly, and let stand to obtain a lithium ion electrolyte.

[0047] Comparative Example 2 (removal of Si(OCH2CF3)4, 1.8 parts of 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione) S1. 32 parts of vinylene carbonate, 18 parts of chloroethylene carbonate, 20 parts of trifluoropropylene carbonate and 1.5 parts of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether are mixed uniformly to obtain a non-aqueous organic solvent; S2: Under an inert gas environment at room temperature, 18 parts of lithium hexafluorophosphate, 2 parts of lithium dioxalatoborate, and 1.8 parts of lithium bis(fluorosulfonyl)imide are added to a non-aqueous organic solvent and stirred until the composite lithium salt is completely dissolved; then 1.2 parts of 2,3-pyridinedicarboxylic anhydride are added, stirred sufficiently, and allowed to stand to obtain a lithium ion electrolyte.

[0048] Comparative Example 3 (Removal of 2,3-pyridinedicarboxylic anhydride) S1. 32 parts of vinylene carbonate, 18 parts of chloroethylene carbonate, 20 parts of trifluoropropylene carbonate and 1.5 parts of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether are mixed uniformly to obtain a non-aqueous organic solvent; S2 Under an inert gas environment at room temperature, 18 parts of lithium hexafluorophosphate, 2 parts of lithium dioxalatoborate, and 1.8 parts of lithium bis(fluorosulfonyl)imide are added to a non-aqueous organic solvent and stirred until the composite lithium salt is completely dissolved; then 2 parts of Si(OCH2CF3)4 and 1.8 parts of 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione are added, stirred thoroughly, and allowed to stand to obtain a lithium ion electrolyte.

[0049] Experimental example 1. Battery cycle performance test (as shown in Table 1).

[0050] Preparation of positive electrode sheet: Lithium cobalt oxide, conductive agent CNT and binder polyvinylidene fluoride in a mass ratio of 95:2.5:2.5 were fully stirred and mixed in N-methylpyrrolidone solvent to form a slurry with a viscosity of 6 000 mPa·s. The slurry was then coated on an 8 μm thick aluminum foil current collector, dried, and cold pressed to obtain a positive electrode sheet.

[0051] Preparation of negative electrode sheet: Graphite, conductive agent acetylene black, binder styrene butadiene rubber and thickener sodium carboxymethyl cellulose in a mass ratio of 95:2.5:1.5:1 were fully stirred and mixed in an appropriate amount of deionized water solvent to form a negative electrode slurry with a viscosity of 3000mPa·s. The slurry was then coated on a 6 μm thick Cu foil current collector, dried, and cold pressed to obtain a negative electrode sheet.

[0052] Preparation of lithium-ion batteries: stack the positive electrode sheet, the isolation film and the negative electrode sheet in order, so that the isolation film is located between the positive and negative electrodes to play an isolation role, and then wind them into a bare battery cell. Thereafter, the bare battery cell is placed in an outer packaging bag, and the electrolytes in the above-mentioned embodiments 1-4 and comparative examples 1-3 are respectively injected into the battery cells, and the corresponding lithium-ion batteries are prepared through vacuum packaging, standing, formation, shaping and other processes.

[0053] Among them, the lithium-ion battery cycle performance test conditions are: voltage of 3.0 ~ 4.5 V, cycle test temperature of 45℃ and 60℃, and charge and discharge rate of 1.0 C.

[0054] Table 1: It can be seen from Table 1 that the batteries prepared using the electrolytes in Examples 1-4 have relatively excellent electrical cycle performance, and the battery capacity retention rate after 600 cycles at 45°C is not less than 93.7%; the battery capacity retention rate after 100 cycles at 60°C is not less than 97.8%, the battery capacity retention rate after 200 cycles at 60°C is not less than 92.3%, and the battery capacity retention rate after 300 cycles at 60°C is not less than 82.2%; while the electrolytes in Comparative Examples 1-3 are not strictly in accordance with the components or dosages in this application, and their cycle performance is significantly poor.

[0055] 2. Thermal thickness expansion rate test of the battery (as shown in Table 2).

[0056] The lithium-ion batteries prepared in Examples 1-4 and Comparative Examples 1-3 were subjected to a high-temperature continuous charging test. The specific test method was as follows: the thickness of the battery cell was tested at room temperature, and after being placed at 60°C for 2 hours, it was charged to 4.5V according to the standard charging method, and no cut-off current was set. The hot thickness was tested after 6 days, 12 days, and 18 days. For safety reasons, if the thickness exceeded 50% or the battery had obvious lithium deposition and pitting, it was necessary to take it out of the high-temperature box and stop the test. Battery cell expansion rate = (continuous charging hot thickness - thickness before entering the box) / (thickness before entering the box) × 100%.

[0057] Table 2 6 days 12 days 18 days Example 1 4.7% 7.5% 13.3% Example 2 4.3% 7.3% 12.7% Example 3 4.5% 7% 12.4% Example 4 4% 6.7% 12.9% Comparative Example 1 >8.5 >15 >23 Comparative Example 2 >8.5 >15 >23 Comparative Example 3 >8.5 >15 >23 It can be seen from Table 2 that the batteries prepared using the electrolytes in Examples 1-4 have relatively excellent anti-thermal expansion effects. In the continuous high-temperature charging test experiment at 60°C, the battery cell expansion rate on the 6th day is not higher than 4.7%, the battery cell expansion rate on the 12th day is not higher than 7.5%, and the battery cell expansion rate on the 18th day is not higher than 13.3%; while the electrolytes in Comparative Examples 1-3 are not strictly in accordance with the components or dosages in this application, and their anti-thermal expansion effects are significantly poor.

Claims

1. A high temperature lithium ion electrolyte, characterized in that: The components include: including non-aqueous organic solvents, lithium salts and additives; The non-aqueous organic solvent includes vinylene carbonate, chloroethylene carbonate and trifluoropropylene carbonate; The lithium salt includes lithium hexafluorophosphate, lithium bis(oxalatoborate), and lithium bis(fluorosulfonyl)imide; The additives include Si(OCH2CF3)4, 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 2,3-pyridinedicarboxylic anhydride.

2. A high temperature lithium ion electrolyte according to claim 1, characterized in that: It includes the following components by weight: 20-35 parts of vinylene carbonate, 15-25 parts of chloroethylene carbonate, 15-25 parts of trifluoropropylene carbonate, 10-20 parts of lithium hexafluorophosphate, 1-5 parts of lithium bis(oxalatoborate), 1-5 parts of lithium bis(fluorosulfonyl)imide, 0.1-5 parts of Si(OCH2CF3)4, 0.1-5 parts of 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 0.1-5 parts of 2,3-pyridinedicarboxylic anhydride.

3. A high temperature lithium ion electrolyte according to claim 2, characterized in that: It includes the following components by weight: 22-33 parts of vinylene carbonate, 16-24 parts of chloroethylene carbonate, 16-23 parts of trifluoropropylene carbonate, 13-20 parts of lithium hexafluorophosphate, 1.5-3.5 parts of lithium bis(oxalatoborate), 1.5-3.5 parts of lithium bis(fluorosulfonyl)imide, 0.5-3 parts of Si(OCH2CF3)4, 0.5-3 parts of 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 0.5-3 parts of 2,3-pyridinedicarboxylic anhydride.

4. A high temperature lithium ion electrolyte according to claim 2, characterized in that: It includes the following components by weight: 25-32 parts of vinylene carbonate, 18-20 parts of chloroethylene carbonate, 18-20 parts of trifluoropropylene carbonate, 15-18 parts of lithium hexafluorophosphate, 2-3 parts of lithium bis(oxalatoborate), 1.8-3 parts of lithium bis(fluorosulfonyl)imide, 1-2 parts of Si(OCH2CF3)4, 1-2 parts of 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 1-2 parts of 2,3-pyridinedicarboxylic anhydride.

5. A high temperature lithium ion electrolyte according to claim 2, characterized in that: It also includes 0.2 to 5 parts of fluorinated ether compounds.

6. A high temperature lithium ion electrolyte according to claim 1, characterized in that: The fluorinated ether compound is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

7. A high temperature lithium ion electrolyte according to claim 5, characterized in that: The fluorinated ether compound is replaced by a modified fluorinated ether compound, wherein the modified fluorinated ether compound is a fluorinated ether compound modified by acrylonitrile or vinyl carbonate.

8. A high temperature lithium ion electrolyte according to claim 7, characterized in that: The preparation method of the modified fluorinated ether compound is as follows: First, add the fluorinated ether compound and azobisisobutyronitrile to an organic solvent, stir thoroughly, then add acrylonitrile or ethylene carbonate, and react thoroughly at 30-40°C for 3-5 hours. After removing the solvent, a modified fluorinated ether compound is obtained.

9. The method for preparing a high temperature lithium ion electrolyte according to any one of claims 1 to 4, characterized in that: The steps include: S1. vinylene carbonate, vinyl chloride carbonate and trifluoropropylene carbonate are mixed uniformly to obtain a non-aqueous organic solvent; S2 In an inert gas environment at room temperature, lithium hexafluorophosphate, lithium dioxalatoborate and lithium bis(fluorosulfonyl)imide are added to a non-aqueous organic solvent and stirred until the composite lithium salt is completely dissolved; then Si(OCH2CF3)4, 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 2,3-pyridinedicarboxylic acid anhydride are added, stirred thoroughly and allowed to stand to obtain a lithium ion electrolyte.

10. The method for preparing a high temperature lithium ion electrolyte according to claim 5, characterized in that: The steps include: S1. vinylene carbonate, chloroethylene carbonate, trifluoropropylene carbonate and a fluorinated ether compound are uniformly mixed to obtain a non-aqueous organic solvent; S2 In an inert gas environment at room temperature, lithium hexafluorophosphate, lithium dioxalatoborate and lithium bis(fluorosulfonyl)imide are added to a non-aqueous organic solvent and stirred until the composite lithium salt is completely dissolved; then Si(OCH2CF3)4, 1-[2-(trimethylsilyl)ethoxycarbonyloxy]pyrrolidine-2,5-dione and 2,3-pyridinedicarboxylic acid anhydride are added, stirred thoroughly and allowed to stand to obtain a lithium ion electrolyte.

Citation Information

Patent Citations

  • An electrolyte and a secondary lithium battery and capacitor containing the electrolyte.

    CN102280664A

  • Additive-containing high-voltage electrolyte for lithium ion secondary battery and preparation method

    CN109818065A

  • Electrolyte film-forming additive and lithium ion battery electrolyte containing additive

    CN113140794A

  • Electrolyte for lithium ion battery and lithium ion battery

    CN113839088A